Fast charging of lithium-ion batteries using peak power estimation - Baduria, John Patrick N.; Odulio, Carl Michael (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
In Lithium-ion battery powered electric vehicles, it is important to keep battery charging both fast and safe. Traditional fast charging methods such as the CC-CV and the pulsed charging protocols provide fixed charging levels regardless of the battery's state and condition. Power estimation uses real time feedback information from the battery to predict the maximum safe charging current. Using an equivalent circuit model and a simplified thermal model, power estimation fast charging is shown to be superior to CC-CV both in charging time and peak temperature, when charging up to 80 percent state-of-charge. A switchover to CC-CV when charging above 80 percent state-of-charge guarantees a full charge, as compared to power estimation charging only. Power estimation fast charging is demonstrated in a series configuration of four cells wherein the effect of practical cell imbalances in thermal response is shown.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Lithium cells; Electric vehicles -- Batteries